Radiology review manual - Dähnert, Wolfgang (Philadelphia : Wolters Kluwer Health/Lippincott Williams Wilkins, 2011)
"The book describes the disease entities, radiologic symptoms., as well as lists of differential diagnosis"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Radiology, Medical -- Outlines, syllabi, etc; Diagnosis, Radioscopic -- Outlines, syllabi, etc; Electronic books